Corporate social responsibility and passengers' behavioral intentions: A case study on railway services. (March 2023) - Rotaris, Lucia; Scorrano, Mariangela; Campisi, Barbara; Rossi, Paola
Abstract: Corporate Social Responsibility (CSR) has become a key factor for businesses to compete in the market and maintain sustainable growth. Although there is abundant literature on the relationship between CSR and customer satisfaction, only a few papers have dealt with the transportation sector. This study fills this gap by analyzing the outcome of engaging in environmental, social, economic, and ethical initiatives in the rail sector. To this aim, we surveyed 2713 customers of Trenitalia, the leading railway operator in Italy. Estimating hybrid discrete choice models, we found that investing in initiatives aimed at creating new jobs, contributing to national economic development, safeguarding the environment, and protecting passengers' safety significantly affects customers' level of satisfaction which is positively related to passengers' loyalty, intention to recommend the service to others, and willingness to pay higher fares.